A query into socio-economic and educational status of the status of physically disabled students in India: Exploring the Educational Challenges Faced by Physically Disabled Students in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Usually, a family would hide their offspring because they fear being outcast if the communityfinds out about them. They wouldn't consider them valuable members of society. That they, too, areintellectually disabled is a belief held by some. Most disabled youngsters are taught by their parents thatthey aren't worthy of having friends their own age. The kids do what they are told because they are afraidof their parents and God's punishment for them. Because schools don't place a high priority onaccommodating students with disabilities, those with physical impairments are less likely to enjoy theirtime spent there. This is true for a wide range of educational factors, including but not limited tocurriculum, instructional materials, infrastructure, special programming (such sports and games),environmental concerns, and overall quality of education, and it is particularly true in poor nations.